DESIGN OF A HEAT EXCHANGER NETWORK BY GRAPH METHOD - Tung, Nguyen Huu (Vietnam Journal of Science and Technology, 2012)
The problem of synthesizing a network of heat exchangers can be resolved by the temperature – enthalpy diagram or by the table method, but they are not convenient in large heat exchanger network design. In this study, we use graph theory to present and to design a heat exchanger network. The developed method is one way to avoid the difficulties inherent with applying temperature – enthalpy diagram or table method to a large complex network and the presentation of network as a grid in graph theory is very clear and allows for easy modification. Key words. Design of heat exchanger network